Industry 5.0 Readiness Assessment: A Maturity Model For Indonesian Companies - Mikhael Chandra Arta; Nikita Fransiska Mandagi; Intan Kurniawan; Edi Abdurachman (Green Publisher Indonesia, 2024)
As times have evolved, there have been significant advancements in various fields, particularly in technology and industry. Rapid progress in the industrial sector has been marked by the phases of the revolution that started from Industry 1.0 to the latest Industry 5.0 which had been introduced in 2019. However not every company is ready to adapt industry 5.0 into their system and behaviors. There is still lack of matrix development to assess company maturity level in industry 5.0. In this paper, three development matrix is developed so it is easier to assess company maturity level from industry 5.0 perspective. The quantitative data is collected by giving questionnaires to several sectors. From the analysis that has been conducted, it is concluded that automotives industry it the most ready sector to adapt with industry 5.0.